Isolation and genotyping of Bartonella henselae in domestic cats from São Paulo and Minas Gerais States, Southeasthern Brazil - Furquim, Maria Eduarda Chiaradia [UNESP] (2021)
Bartonella henselae is the causative agent for the infectious disease Cat Scratch Disease (CSD), which can be fatal. Domestic and wild felines are known to be its main mammal reservoirs. The present study aimed to investigate the occurrence and genetic diversity of Bartonella spp. in cats sampled in São Paulo (SP) and Minas Gerais (MG) States, Southeastern Brazil. Based on a quantitative real-time PCR (qPCR) assay, a Bartonella sp. nuoG gene fragment was detected in 39.9% (122/306) of the blood samples (46/151 cats of SP; 76/155 cats of MG). The blood samples were submitted to a pre-enrichment culture technique that allowed the detection of 12 additional positive samples, which showed to be negative in the qPCR using DNA blood samples as templates. Furthermore, five B. henselae isolates were obtained from qPCR-negative samples for both blood and pre-enrichment culture. Seven out of 24 Ctenocephalides felis fleas were positive for Bartonella spp. in the qPCR assay; 4/7 positive fleas were collected from Bartonella-negative cats. Twenty-three rpoB B. henselae cloned sequences were obtained from nine cats’ blood samples, showing the occurrence of 13 different genotypes. Median-joining network and SplitsTree distance analysis showed that the obtained sequences represented distinct B. henselae genotypes when compared to those previously deposited in GenBank. Intra-host diversity was found, since different rpoB genotypes of B. henselae were detected in individual single cats. Bartonella henselae isolates showed two allelic profiles (ST37 in cats from MG state and ST9 in SP state) by MLST (Multilocus Sequence Typing) based on sequencing of eight molecular markers. The present study is the first molecular report of Bartonella sp. in cats from Minas Gerais State. In summary, this body of work showed the occurrence of different B. henselae rpoB genotypes at an intra-reservoir host level. Based on qPCR from blood samples and pre-enrichment liquid culture and isolation, occurrence of 33.1% (50/151) and 56.8% (88/155) for Bartonella sp. was found in cats from SP and MG states, respectively. Two different allelic profiles of B. henselae were found in cats from the states of São Paulo (ST9) and Minas Gerais (ST37), suggesting a clonal evolution of bartonellae in a certain geographical region.